PENGEMBANGAN LEMBAR KEGIATAN SISWA BERBASIS CHALLENGE BASED LEARNING PADA MATERI PELUANG - Putri Cahyani Agustine; Fitri Apriani (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2021)
This research aims to produce development products and determine the feasibility of student activity based on challenge based learning worksheet opportunities material in grade 8 at SMP Negeri 5 Pangkalpinang. This research is a development research through two stages, first the preliminary stage consist of preparation and design. The Second is formative evaluation stage consist of self-evaluation, expert reviews, one-to-one, small group, and field test. This research produce Challenge Based Learning worksheet in opportunities material and sample consist of 38 students. The technique of collecting data by observation sheets, questionnaires, tests, and documentation. The data is analyzed so that the resulting instrument is valid and practical. Valid is described based on the validator's assessment in terms of content, construct, and language. Practicality is illustrated by the trial results at the small group stage. From the results of data analysis, the feasibility of the contents of the 3.55 categories is very good, the feasibility of serving 3.65 categories is very good, and the language feasibility is 3.12 categories are good. From the research results have produced LKS based challenge based learning on opportunity material.